The Forecasting of Military Expenditure in Saudi Arabia in Terms of Military Security - Bartosz Kozicki; Jarosław Zelkowski; Szymon Mitkow; Mariusz Gontarczyk (Polish Political Science Yearbook, 2022)
The study attempts to forecast military expenditure in Saudi Arabia for 2020. The research began with a comparative analysis of military expenditure in Saudi Arabia and Russia between 2000–2019. For this purpose, bar charts were used on which the calculated values of the dynamics indices with a fixed (2000) and movable (previous year) base of the considered primary data were outlined. The study was preceded by constructing a multiple regression model to evaluate the impact of the increase in military expenditure in Russia on Saudi Arabia. This model shows that as military spending in Russia increases by one million dollars, military spending in Saudi Arabia increases by $ 0.085 million. Then, data on the expenditure incurred by both analyzed countries in 2020, obtained from various internet sources, was outlined. Their analysis made it possible to select only qualitative methods in the form of expert opinions for the forecast. Saudi Arabia's military expenditure forecast was $ 57 500 million.